Factors Influencing the Continuous Use of Cloud Computing Services in Organization Level - Al-Sharafi, Mohammed A.; Ruzaini, Abdullah Arshah; Abu-Shanab, Emad A. (ACM New York, 2017)
The primary purpose of carrying out this research work is to identify the crucial factors that influence the continuous use of cloud computing services in organizations. To achieve this identified objective, this research work carried out a comprehensive literature review on cloud computing services‘ adoption at the organizational level, particularly emphasizing the factors that define the prolonged adoption of cloud computing services. The factors identified, served as a guide required by organizations for completely safe and effective cloud computing service and their use in businesses. This research adopts the criteria of Wymer and Regan as a basis for this study. A total of 53 factors were obtained from prior studies on the cloud computing services‘ adoption. Results obtained during the cause of study revealed that the most crucial factors affecting the continuous use of cloud computing services in organizations areas follows: Relative advantage; Complexity: Perceived security and privacy; Compatibility; Top manager‘s support; Cost reduction; Competitive pressure; IT readiness; Firm size; Vendor support; Regulations and Government policy; Trialability; Perceived reliability; Perceived availability; Uncertainty and Perceived Trust.